Integrating the social sciences into the COVID-19 response in Alberta, Canada. Issue 7 (27th July 2020) - Leslie, Myles; Fadaak, Raad; Davies, Jan; Blaak, Johanna; Forest, PG; Green, Lee; Conly, John
Abstract : This paper outlines the rapid integration of social scientists into a Canadian province's COVID-19 response. We describe the motivating theory, deployment and initial outcomes of our team of Organisational Sociologist ethnographers, Human Factors experts and Infection Prevention and Control clinicians focused on understanding and improving Alberta's responsiveness to the pandemic. Specifically, that interdisciplinary team is working alongside acute and primary care personnel, as well as public health leaders to deliver 'situated interventions' that flow from studying communications, interpretations and implementations across responding organisations. Acting in real time, the team is providing critical insights on policy communication and implementation to targeted members of the health system. Using our rapid and ongoing deployment as a case study of social science techniques applied to a pandemic, we describe how other health systems might leverage social science to improve their preparations and communications.